استراتيجيات تعليم اللغة العربية باستخدام نظرية الذكاءات المتعددة لمنيب شاطب: Arabic - Ritonga, Ade; Rahmat Raja; Ahmad Zaky (Tatsqifiy: Jurnal Pendidikan Bahasa Arab, 2025)
This article aims to describe the application of the educational concept based on the "Multiple Intelligences" theory proposed by Munif Chatib in Arabic language teaching strategies. The implementation of this approach stems from the need for an instructional model that can accommodate the diversity of students’ intelligences, making the learning process more effective, enjoyable, and meaningful.The article employs a qualitative descriptive method, with data collected from both primary and secondary sources using document analysis. It includes a review of relevant literature, such as the works of Howard Gardner. As a practical contribution from the author, a model of instructional design and a Lesson Implementation Plan (RPP) was developed to align with the various types of intelligences.The findings indicate that applying a multiple intelligences-based teaching strategy in Arabic language education contributed to creating a more interactive and dynamic learning environment. Students became more engaged and demonstrated better understanding when instructional methods were aligned with their dominant intelligences, such as linguistic, logical-mathematical, kinesthetic, musical, and interpersonal intelligences.In conclusion, the use of the multiple intelligences theory not only enhances the quality of education, but also ensures educational equity by addressing individual differences among learners. Therefore, this strategy is worthy of further development and broader implementation, particularly in the field of Arabic language education.